Exploitation Of Love In The Sonnets Of Shakespeare (1609): A Sociological Approach - Setyawan, Yogi Daniar, Dr. M. Thoyibi, M.S, Siti Fatimah, S. Pd, M. Hum (2014)
This research paper aimed to show visible image of Shakespeare‟s Sonnets which analyzed by using a sociological approach. The objective of the research are to analyzing the sonnet based on the structural element and to analyzed the sonnets based on sociological perspective by indentifying from relationship between social historical background of English in late sixteenth century. This research paper belongs to qualitative research. Data of the research is the text from and it has taken based on the theme, thereabout consisting 23 sonnets a thematically. The primary data of the research is the Shakespeare‟s Sonnets from the book with entitled The Sonnets of Shakespeare by Thomas G Thorpe and secondary data of the research are biography of the author, websites, and other source about the sonnets, the social background of English society that support the analysis. The method to analyze of this data is descriptive analysis. The researcher comes to the conclusion as follows. Based on the sociological analysis, it is evident that Shakespeare exploited love theme in his sonnets. The exploitation of love themes was related to the upper class culture to which he belonged in which literature was considered as the main factor of civilized society. Literature became important of individual social strata in the society.